Celastrol alleviates diabetic vascular injury via Keap1/Nrf2-mediated anti-inflammation - An, Ning; Wang, Rixiang; Li, Lin; Wang, Bingyu; Wang, Huiting; Peng, Ganyu; Zhou, Hua; Chen, Gen (Frontiers in Pharmacology, 2024)
Introduction: Celastrol (Cel) is a widely used main component of Chinese herbal medicine with strong anti-inflammatory, antiviral and antitumor activities. In the present study, we aimed to elucidate the cellular molecular protective mechanism of Cel against diabetes-induced inflammation and endothelial dysfunction. Methods: Type 2 diabetes (T2DM) was induced by db/db mice, and osmotic pumps containing Cel (100 μg/kg/day) were implanted intraperitoneally and were calibrated to release the drug for 28 days. In addition, human umbilical vein endothelial cells (HUVECs) were cultured in normal or high glucose and palmitic acid-containing (HG + PA) media in the presence or absence of Cel for 48 h. Results: Cel significantly ameliorated the hyperglycemia-induced abnormalities in nuclear factor (erythroid-derived 2)-like protein 2 (Nrf2) pathway activity and alleviated HG + PA-induced oxidative damage. However, the protective effect of Cel was almost completely abolished in HUVECs transfected with short hairpin (sh)RNA targeting Nrf2, but not by nonsense shRNA. Furthermore, HG + PA reduced the phosphorylation of AMP-activated protein kinase (AMPK), the autophagic degradation of p62/Kelch-like ECH-associated protein 1 (Keap1), and the nuclear localization of Nrf2. However, these catabolic pathways were inhibited by Cel treatment in HUVECs. In addition, compound C (AMPK inhibitors) and AAV9-sh-Nrf2 reduced Cel-induced Nrf2 activation and angiogenesis in db/db mice. Discussion: Taking these findings together, the endothelial protective effect of Cel in the presence of HG + PA may be at least in part attributed to its effects to reduce reactive oxygen species (ROS) and inflammation through p62/Keap1-mediated Nrf2 activation.